Analytical robust tuning of PI controllers for first-order-plus-dead-time processes - Alfaro, V.M.; Vilanova, R.; Arrieta, O. (2008 IEEE International Conference on Emerging Technologies and Factory Automation, 2008)
This paper presents an analytically deducted procedure for tuning two-degree-of-freedom proportional integral (PI) controllers for first-order-plus-dead-time (FOPDT) controlled process. The equations incorporate a design parameter, which relates the feedback control systempsilas time constant, with the controlled process time constant. The design procedure considers the control-loop robustness by means of maximum sensitivity requirements, allowing the designer to deal with the performance-robustness trade-off.